PENGARUH SIKAP MANDIRI, MOTIVASI DAN RASA PERCAYA DIRI TERHADAP MINAT BERWIRAUSAHA GENERASI MUDA DI KABUPATEN BREBES - Fifi Ayu Wulandari; Sutrisno; M. Fadjar Dharmaputra (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
The research carried out aims to test and analyze the impact of independent attitudes, motivation and self-confidence on the entrepreneurial interest of the younger generation. The respondents in the research carried out were the young generation in Brebes Regency, totaling 172 people. Data was obtained by distributing online questionnaires via Google Form to the young generation in Brebes Regency. The design applied is a quantitative method and applies census or saturated sampling techniques. The research was conducted applying multiple linear regression analysis methods. The results of the research carried out show that there is a positive and significant impact between independent attitudes for the younger generation's entrepreneurial interest, there is a positive and significant impact between motivation for the younger generation's entrepreneurial interest, there is a positive and significant impact between self-confidence for the younger generation's entrepreneurial interest, and simultaneously there is an influence independent variable for the dependent variable.